Komparasi FTK Imager dan MOBILedit Forensic Express Pro dalam Investigasi Cyberbullying Instagram Menggunakan Framework ACPO - Fahmi Fachri; Anisa Nur Hidayah (JSAI (Journal Scientific and Applied Informatics), 2026)
Cyberbullying is one of the most common forms of cybercrime occurring on social media platforms, including Instagram through the Direct Message (DM) feature. This study aims to conduct a digital forensic investigation of Cyberbullying cases on Instagram using the Association of Chief Police Officers (ACPO) framework and to compare the performance of FTK Imager and MOBILedit Forensic Express Pro in obtaining digital evidence from Android devices. The research method was carried out through the stages of plan, capture, analysis, and presentation based on the ACPO framework. The investigation process included data acquisition, data extraction, digital artifact recovery, and digital evidence integrity validation using MD5 and SHA1 hashing methods. The results showed that FTK Imager successfully recovered text messages and voice messages with a recovery success rate of 50%, while MOBILedit Forensic Express Pro successfully recovered photos and videos with a recovery success rate of 50%. The integrity validation results indicated that the digital evidence remained valid and unchanged throughout the investigation process. Based on the comparison results, both tools demonstrated different capabilities in recovering specific digital artifacts. Therefore, the combined use of FTK Imager and MOBILedit Forensic Express Pro can improve the effectiveness of digital forensic investigations and provide more comprehensive digital evidence in Cyberbullying cases on Instagram.